Impact of Electron Acceptor Availability on Methane-Influenced Microorganisms in an Enrichment Culture Obtained From a Stratified Lake - van Grinsven, Sigrid; Sinninghe Damsté, Jaap S.; Harrison, John; Villanueva, Laura (Frontiers in Microbiology, 2020)
Methanotrophs are of major importance in limiting methane emissions from lakes. They are known to preferably inhabit the oxycline of stratified water columns, often assumed due to an intolerance to atmospheric oxygen concentrations, but little is known on the response of methanotrophs to different oxygen concentrations, as well as their preference for different electron acceptors. In this study, we enriched a methanotroph of the Methylobacter genus from the oxycline and the anoxic water column of a stratified lake, that was also present in the oxic water column in winter. We tested the response of this Methylobacter-dominated enrichment culture to different electron acceptors, i.e. oxygen, nitrate, sulfate and humic substances, and found that in contrast to earlier results with water column incubations, oxygen was the preferred electron acceptor, leading to methane oxidation rates of 45 - 72 pmol cell-1 day-1. Despite the general assumption of methanotrophs preferring microaerobic conditions, methane oxidation was most efficient under high oxygen concentrations (>600 μM). Low (<30 μM) oxygen concentrations still supported methane oxidation, but no methane oxidation was observed with trace oxygen concentrations (<9 μM) or under anoxic conditions. Remarkably, the presence of nitrate stimulated methane oxidation rates under oxic conditions, raising the methane oxidation rates by 50% when compared to oxic incubations with ammonium. Under anoxic conditions no net methane consumption was observed, however, methanotroph abundances were 2-3 times higher in incubations with nitrate and sulfate compared to anoxic incubations with ammonium as N-source. Metagenomic sequencing revealed the absence of a complete denitrification pathway in the dominant methanotroph Methylobacter, but the most abundant methylotroph Methylotenera seemed capable of denitrification, which can possibly play a role in the enhanced methane oxidation rates under nitrate-rich conditions.